STUDY DETAIL ENGINEERING DESIGN ( DED ) BANGUNAN GEDUNG HOTEL SHEO DI BANDUNG - Dody Kusmana (ENSAINS JOURNAL, 2019)
Abstract: Study Author's Engineering Detail Design at PT. Buff Buana Kriyasa. PT.ini has tested the Hotel Sheo Building on Monday-Saturday 11 to March 16, 2019 which was witnessed by Hotel Technicians. With the aim of planning, testing, and measuring the feasibility of hotels in the city of Bandung. For example, the author planned this one of them at the Sheo Hotel, including the Condition of Buildings, Rooms, Guest Rooms, BaseCame, Hotel Pages, Regions and Land strength. So that the establishment of hotels can be relied upon, and become an attraction for guests who come to the Hotel. So that hotels in the city of Bandung become an inn, a meeting event, which can satisfy the visitors. Besides that it is a hotel that is included as a favorite, with its territory in a strategic area, and has the strength of a sturdy and attractive building. So there is no need to worry. Therefore, the author will describe the Hotel planning problem by conducting tests including taking Profometer, Hammer Test, and Ultrasonic Pulse Velocity. Herewith, the author will describe the results of the tests that present the objectives, the results of field testing. So that interested parties and contributors are satisfied and helpful about the planning. For the smooth running of this work and also the opportunity given, the author is very useful to support the path of planning the Hotel Building in Bandung Keywords: Detail Engineering, Hotel Sheo, Ultrasonic Pulse Velocity. Abstrak: Study Detail Engineering Desaign Penulis lakukan di PT.Sangga Buana Kriyasa. PT.ini  telah  melakukan pengujian Gedung Hotel Sheo pada hari Senin-Sabtu 11 s/d 16 Maret 2019 yang disaksikan oleh Teknisi Hotel. Dengan tujuan untuk merecanakan, mengetes, dan mengukur kelayakan dari Hotel yang ada di Kota Bandung. Sebagai contoh Penulis melakukan perencanaan ini salah satunya pada Hotel Sheo, meliputi Kondisi Bangunan, Ruangan, Kamar Tamu, BaseCame, Halaman Hotel, Wilayah dan kekuatan Tanah. Supaya pendirian Hotel dapat diandalkan, dan menjadi daya tarik untuk para Tamu yang datang ke Hotel tersebut. Sehingga Hotel di Kota Bandung menjadi sebuah penginapan, acara pertemuan, yang dapat memuaskan para pengunjungnya. Disamping itu merupakan Hotel yang termasuk favorit, dengan wilayahnya ada di wilayah Strategis, serta mempunyai kekuatan Bangunan Gedung yang Kokoh dan menarik. Sehingga tidak perlu dikhawatirkan Maka dari itu Penulis akan menguraikan tentang masalah perencanaan Hotel tersebut dengan melakukan Pengujian meliputi pengambilan Profometer, Hammer Test, dan Ultrasonic Pulse Velocity. Bersama ini Penulis akan menguraikan hasil pengujian tersebut yang menyajikan tujuan, hasil pengujian lapangan. Sehingga pihak yang berkepentingan dan berkontribusi merasa puas dan membantu tentang perencanaan tersebut.untuk kelancaran pekerjaan ini dan juga kesempatan yang diberikan, kepada Penulis sangat bermanfaat untuk mendukukung jalannya perencanaan Bangunan Gedung Hotel yang ada di Kota Bandung. Kata Kunci : Detail Engineering, Hotel Sheo, Ultrasonic Pulse Velocity